Narratives of Experiences in International Teaching Practicum: Lessons from an EFL Pre-Service Teacher - Megawati, Fika; Shah , Shanina Sharatol Ahmad; Anugerahwati , Mirjam; Ubaidillah , M. Faruq; Mustofa , Mutmainnah; Agustina, Sheila (Journal of English Education and Teaching, 2023)
Contrary to popular belief that field experience should be held in local settings, teacher education programs currently initiate networking with other countries through the international teaching practicum (ITP) program. Considering the platform’s magnitude, this paper aims to explore the pre-service English teacher’s experiences during ITP to build professional development of EFL potential teachers from various activities abroad. In this study, a narrative inquiry was implemented and supplemented with data obtained from Tina (pseudonym), an EFL pre-service teacher in one of the Indonesian universities who joined a four-month ITP program abroad, particularly in Thailand. In collecting the data, semi-structured in-depth interviews that emphasized five eligibility aspects were used. The findings reveal that the pre-service teacher reaped plenty of meaningful experience from ITP in terms of the classroom situation, the implementation of basic teaching skills, the period of success or failure in teaching, values for EFL teacher candidates in ITP, critical incidents, and students’ general English competence after ITP. This study provides evidence and feedback for the institution for better planning and organization in implementing practicum. Further, it implies equipping student-teachers with sufficient skill and competence related to adaptability, cultural identity, fear, and emotions in facing challenging English instruction in the future through multiple exposures to teaching instruments and supporting situated environment facilities.